Negotiating hetero-sex : sex, gender, and consent - Seet, Chloe (2018)
Despite ideals of consent being now arguably at its best, the last year has seen an explosion of reports on various forms of sexual violence. This research interrogates the process of hetero-sexual learning to uncover the underlying forces of hetero-sexual violence. It asks: How is the process of sexual learning gendered? What impact does this have on male and female sexualities and their relationship to one another? Using sexual script theory, this research demonstrates how gendered sexual scripts produce gendered sexual sensibilities that disadvantage women in negotiating hetero-sex; and how negating this disadvantage involves overcoming the incognisance of sex as an interaction, that is, between two thinking, feeling individuals who possess different sensibilities about it. In uncovering the deep-rooted inequalities that underpin hetero-sexual violence, this study draws attention to the limits of consent in contemporary society.